Indoor Gardening with Automatic Irrigation System using Arduino Microcontroller - Lamsen, Febrey C; Favi, Jonathan C; Castillo, Baby Hideliza F (ASEAN Multidisciplinary Research Journal, 2022)
Gardening is one of the simplest ways to spend time which, oftentimes, provides a means of working out during weekends, exercising creativity, and giving appreciation to the environment for individuals engaged in this activity. Anyone can do gardening as long as the basic needs of the plants are provided like water, soil, air, sunlight and proper nutrients. Provisions of these necessities are possible with the aid of an automatic irrigation system. This system primarily provides a means of monitoring the status of plants that need to be watered once it is needed. This automatic system will also lessen the efforts of manual nursing of the plants. The researchers implemented a project entitled “Indoor Gardening with Automatic Irrigation System Using Arduino Microcontroller”. The focus of this study was to develop an automatic irrigation system for an indoor garden that uses a moisture sensor to detect the soil humidity and an Arduino microcontroller to regulate the flow of water that irrigates the garden. Specifically, the study achieved to identify the system requirement necessary to develop the proposed project and build the proposed project with suitable features. The study also aimed to determine the major issues and challenges related to system implementation, perform tests and evaluate the accuracy of the proposed project. Researchers made use of a system methodology called Systems Development Life Cycle (SDLC), which was used as a guide in developing the project. This methodology involved four phases: planning, analysis, design, and implementation. Testing was conducted to test the different ranges of moisture content of the soil variable and evaluate the accuracy of the system in delivering water to the subject which is the plant. Results were satisfying in terms of the overall process of the system